Philodina gregaria Murray 1910 - LUKASHANETS, Dzmitry A.; VEZHNAVETS, Vasily V.; MAYSAK, Natalia N.; HIHINIAK 1, Yury H.; BORODIN, Oleg I.; MIAMIN, Vladislav Ye.; GAIDASHOV, Alexey A.; NIKITIUK, Leonid A. (Zenodo, 2019)
Philodina gregaria Murray, 1910 (Fig. 3B) Philodina gregaria Murray, 1910: 42 – Dartnall & Hollowday 1985: 33, Donner 1965: 202, Kutikova 2005: 221 Published as part of LUKASHANETS, Dzmitry A., VEZHNAVETS, Vasily V., MAYSAK, Natalia N., HIHINIAK 1, Yury H., BORODIN, Oleg I., MIAMIN, Vladislav Ye., GAIDASHOV, Alexey A. & NIKITIUK, Leonid A., 2019, Rotifers (Rotifera) from the inland waters and terrestrial habitats of East Antarctic oases (Enderby Land and Prydz Bay), pp. 67-86 in Fragmenta Faunistica 62 (2) on page 75, DOI:10.3161/00159301FF2019.62.2.067, http://zenodo.org/record/6252396